الدراسة التحليلية للعناصر الخاضعة للانعطاف من البيتون المدعَّم بألياف فولاذية - رامية بديع غالية (Tishreen University, 2019)
انتشر استخدام البيتون الليفي في الآونة الأخيرة لميزاته وتفوقه على البيتون العادي خاصة عند استخدامه في المنشآت الهامة منها، والتي تكثر فيها الحالات الحرجة، ويتم حساب المقاطع وفق الطريقة الحدية باعتماد مخطط  (σ-ε)   لكن في حالة البيتون الليفي. من الضروري الأخذ بالحسبان أثر وجود الألياف في هذا المخطط ومن ثمة في  مقاومة المقاطع، حيث تعرضنا إلى دراسة حساب العناصر المستطيلة الخاضعة لللانعطاف من البيتون المدعم بألياف فولاذية.   الهدف من هذا البحث هو دراسة تأثير خطأ استبدال مخطط إجهادات الضغط في البيتون المدعم بألياف فولاذية بمستطيل مكافئ أبعاده δ×f'c و β×x حيث تعد كل من δ و  β  مساوية لـ 0.85، بدلاً من استخدام القيم الحقيقية الخاصة بحالة البيتون الليفي، ومن ثم الدراسة التحليلية للعناصر المستطيلة الخاضعة للانعطاف وإيجاد المعادلات بالحالة العامة بإدراج هذين الثابتين فيها،وإظهار الفرق بالأمثلة. وقد اعتمدت الطريقة على تحديد أبعاد مستطيل الضغط بحيث  تكون مساحته تساوي مساحة مخطط إجهاد التشوه للبيتون ومركز ثقله مطابق لمركز ثقـل المخطط الأصلي. The use of fiber reinforced concrete has recently spread due to its  characteristics and its superiority to ordinary concrete, specially when used in important constructions, with many critical cases, and in which calculation of the sections is done using the limited method of (σ - ε) curve of fiber reinforced concrete. It is necessary to consider the effect of fibers existence  on the curve and the strength of sections. This paper studies the rectangular elements, which submit to bending of steel fiberreinforced concrete. It also examines the error which results from the substitution of actual stress block of steel fiber reinforced concrete with an equivalent rectangular stress block with dimensions of  δ×f'c  , β×x which consider that δ=β=0.85 instead of the real parameters that had been dedused. It then studies the rectangular members which submit to bending of steel fiber reinforced concrete, and create the equations with the real parameters. In order to show the difference with examples, we dedused the relationship of rectangular stress block in function to the compression strength in terms of the reinforcing index (Vf.L/f): (Vf%Volume Fraction - L/f Aspect Ratio ). We realized a constitutive equation describing the behavior of the steel fiber reinforced concrete. This research aims to define the parameters of rectangular stress block by realizing that the essential attributes of the equivalent rectangular stress block shoud have the same area and centroidal height as those of the actual stress block.